ANALISIS IMPLEMENTASI PROGRAM JKN PADA PESERTA BANTUAN IURAN (PBI) ATAU MASYARAKAT MISKIN PADA WILAYAH INDONESIA - Thalitha Zulaika; Dina, Nadila Chairani, Riantania Sinaga, Fitriani Pramita Ginting (CV. Adiba Aisha Amira, 2024)
One of the state investments that needs attention is the health sector, because it is closely related to the Human Resource Development Process. The fate of the nation really depends on it. The aim of this literature study was to examine the form and outcomes of evaluating health financing policies for the poor in the JKN program in various regions in Indonesia, based on identified concerns and in accordance with their urgency. This article was prepared using the literature review method, namely summarizing and explaining the contents of previously published sources of findings in accordance with the topic of the author's analysis regarding the implementation of the JKN program among contributory assistance (PBI) participants or underprivileged communities in the regions. Articles from 2019 to 2023 are used as references, using Google Scholar, Garuda Journal, and Springer Link. The JKN program does not reach everyone, especially the poor, who cannot obtain fair and adequate health protection. And as those in need, all poor people must be prioritized. because they do not get or qualify for government support. To complement the National Social Security System which is not yet able to cover all underprivileged and poor communities, regional and central governments must create regional health insurance programs.